FORTIFICATION OF EDIBLE MUSHROOMS (Pleurotus ostreatus) WITH CALCIUM, SELENIUM AND VITAMIN C - CORTÉS R., Misael; GARCÍA S., Andrea; SUÁREZ M., Héctor (Vitae, 2009)
Matrix engeneering is a methodology to obtain functional foods that applies the vacuum impregnation technique in order to incorporate physiologically active components into the food porous structure. The objective of this study was to develop a minimally processed product with functional characteristics by means of fortification of the mushroom Pleurotus ostreatus with calcium, selenium and vitamin C. Fortification levels for Ca and Se of 7,3 and 42,3% of the Daily Recommended Intake (DRI)/100 g of fresh mushroom, respectively, were obtained. At the beginning of the storage (4º C, 83% relative moisture), the vitamin C contents was 40% of the DRI/100g of fresh mushroom, and during storage, zero-order degradation kinetics was adjusted. The soft face of fortified mushrooms showed more browning than the rugged one (lesser luminosity values - L*), and more red (a* bigger value). Texture of the fortified product was not influenced by the impregnation dissolution but, with time, samples became harder.